2022
DOI: 10.1177/17455057221139660
|View full text |Cite
|
Sign up to set email alerts
|

Menopause knowledge and education in women under 40: Results from an online survey

Abstract: Background: All women experience the menopause, yet education around the topic is limited. Studies conducted in women aged over 40 show that women have limited knowledge about the menopause. Objectives: This study aims to understand what women under 40 know about the menopause, how they have acquired this knowledge and where they think menopause education should be taught. This data will help to determine how to effectively deliver menopause education. Design: A survey was designed that asked women under 40 wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…We are optimistic that this situation will be improved in the UK now that menopause education has been added to schools' RSE curriculum. 15 In our survey of women under 40, we found slightly more knowledge than women over 40 (7) but we need to be at a point where all women feel very informed.…”
Section: Women's Educationmentioning
confidence: 87%
See 3 more Smart Citations
“…We are optimistic that this situation will be improved in the UK now that menopause education has been added to schools' RSE curriculum. 15 In our survey of women under 40, we found slightly more knowledge than women over 40 (7) but we need to be at a point where all women feel very informed.…”
Section: Women's Educationmentioning
confidence: 87%
“…It was clear that many women in this study were uninformed about the menopause and had not been taught about it at school, which was similar to what we found in perimenopausal women 6 and women under 40. 7 An Italian study analysing women aged 45-60 years found that more than half of the participants did not receive any information about menopause and possible therapies, and those who did, often rated it as poor and contrasting. 13 Research has demonstrated the direct correlation between the severity of menopausal symptoms and a woman's level of knowledge.…”
Section: Women's Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…A study indicated 75% of women under 40 believed menopause should be taught in schools. 40 Studies show including boys in menstrual education normalises menstruation and conveys an understanding of what peers and family members are going through. 19,40 The UK’s updated secondary school RSHE curriculum (introduced in 2019) indicates that students should understand reproductive health ‘and menopause’ 56 – a phrase that reads as though menopause was tacked on as an afterthought.…”
Section: Discussionmentioning
confidence: 99%